Relationship Between Life Satisfaction and Nutrition of Students at the Faculty of Sports and Health Sciences at University - Yılmaz, Taner; Dalbudak, İbrahim; Yiğit, Şıhmehmet (Progress in Nutrition, 2020)
In this study, it is aimed to examine the relationship between life satisfaction and nutrition of the students studying at the faculty of sports and health sciences at university. 407 students, 244 women and 163 men, who study at the Faculty of Sport Sciences at Uşak University and the Faculty of Health Sciences in the 2018 - 2019 academic year participated in the study. In this study, "Three Factor Nutrition Scale" was used to evaluate the nutritional habits of students, and "Life Satisfaction Scale" was used to measure life satisfaction. “Personal Information Form” was used to evaluate the data regarding the demographic characteristics of university students. In analyzing the data, SPSS 22.0 program was used and frequency distributions were created. While total scores of life satisfaction scale do not differ according to age, gender, faculty and economic condition variables (p> 0.05), there are significant differences according to academic success, future expectation and loneliness level variables (p According to the scores of the nutrition scale; while there is a significant difference according to their age, gender, faculty, loneliness level (p 0.05).> There is no statistically significant relationship between life satisfaction and nutrition (p